Implementing Local Server Migration to Free Hosting to Increase Web Service Availability - Arif Hidayat; Ismail Puji Saputra (Journal of Vocational, Informatics and Computer Education, 2026)
Objective - This research aims to implement the migration of on-premises servers to a hosting service to improve the availability and accessibility of a student data management application. Methods - The approach used is the Network Development Life Cycle (NDLC) framework, which includes the stages of analysis, design, simulation, implementation, monitoring, and management. The success of the migration was evaluated by validating the integrity of all directory files, synchronizing records in the MySQL database, and testing the functionality of the application's navigation features in the new server environment. Findings - The test results indicate that the migration was successfully implemented in accordance with the established technical parameters. Monitoring data over ten days showed an average response time ranging from 1.2 to 2.5 seconds, with an average service availability (uptime) of 98.7%. Research Implications - These findings confirm that hosting services can be an efficient infrastructure solution for developers or institutions to distribute small-scale applications globally without significant initial costs. Conclusion - The application of the NDLC methodology provides a systematic approach to ensuring the smooth transition of data from on-premises to the cloud. Despite the high availability level, it is recommended to consider infrastructure scalability in the event of a significant increase in traffic in the future